Enhancing Patient Care: The Role Of Radiology Nurses In Modern Healthcare (Journal of Namibian Studies : History Politics Culture, 2023)
Radiology nursing plays a critical role in modern healthcare, bridging the gap between patient care and advanced imaging technology. This article explores the multifaceted responsibilities of radiology nurses, emphasizing their role in patient advocacy, safety protocols, collaboration, and continuity of care. Radiology nurses serve as advocates for patients, providing education, support, and ensuring their safety throughout imaging procedures. They collaborate with interdisciplinary teams, communicate imaging findings, and facilitate seamless transitions in care. Specialized training equips radiology nurses with the skills to administer contrast agents safely, monitor patients, and uphold radiation safety measures. By embracing these principles, radiology nurses contribute to the delivery of high-quality, patient-centered care in the radiology department and beyond.